Abrasion-resistant copper core cable and method of making same
Patent Information
- Application Number
- CN202310488351.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-04
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2043-05-04
AI Technical Summary
[0003]而传统的电缆材料难以满足高频弯曲和摩擦的要求,易受到外力的损伤和磨损,从而影响电缆的使用寿命,并且安全隐患大,传统电缆的绝缘层和护套材料容易熔化或燃烧,引发火灾,于是我们需要对材料进行改进,同时优化电缆结构,以提高电缆的耐磨性能
1.本发明的耐磨铜芯电缆及其制备方法,以电缆导体作为中心,由内而外依次包覆设置内半导体屏蔽层、绝缘层、外半导体屏蔽层、铜带绕包屏蔽层、阻燃层、内衬层、镀锌钢带铠装层、耐磨护套层;其中内半导体屏蔽层和外半导体屏蔽层能够有效地防止电缆中的电场和磁场干扰周围的设备和电路,提高电缆的抗干扰性能和信号传输质量;绝缘层为聚氯乙烯,具有良好的绝缘性能和耐电压能力,能够保证电缆的安全可靠运行;铜带绕包屏蔽层能够进一步提高电缆的屏蔽性能,减少电缆外界的电磁干扰;阻燃层能够有效地防止电缆在火灾中的燃烧和蔓延,提高电缆的安全性能;内衬层和耐磨护套层能够保护电缆的内部结构和外部表面,提高电缆的耐磨性能和使用寿命。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of cable technology, specifically to a wear-resistant copper core cable and its preparation method. Background Technology
[0002] Copper core cables are widely used in power, telecommunications, and construction industries. They consist of a copper conductor, insulation layer, and sheath. With the continuous development of these sectors, copper core cables are constantly evolving and improving to meet the needs of different fields. For example, in the power sector, high-voltage and ultra-high-voltage cables are being developed to improve the efficiency and distance of power transmission; in the telecommunications sector, new types of cables such as optical fibers are being developed to meet the demands of high-speed communication; and in the construction sector, special cables with fire resistance, waterproofing, and corrosion resistance are being developed to ensure the safety and reliability of buildings. Today, copper core cables have become one of the mainstream products in the wire and cable industry, providing reliable power and communication support for the development and progress of various fields.
[0003] Traditional cable materials are difficult to meet the requirements of high-frequency bending and friction, and are easily damaged and worn by external forces, which affects the service life of the cable and poses a great safety hazard. The insulation layer and sheath material of traditional cables are prone to melting or burning, causing fires. Therefore, we need to improve the materials and optimize the cable structure to improve the wear resistance of the cable.
[0004] Therefore, we propose a wear-resistant copper core cable and its preparation method. Summary of the Invention
[0005] The purpose of this invention is to provide a wear-resistant copper core cable and its preparation method to solve the problems mentioned in the background art.
[0006] To solve the above-mentioned technical problems, the present invention provides the following technical solution: A wear-resistant copper core cable, wherein the cable is centered on the cable conductor and is sequentially covered from the inside out with an inner semiconductor shielding layer, an insulation layer, an outer semiconductor shielding layer, a copper tape wrapping shielding layer, a flame-retardant layer, an inner lining layer, a galvanized steel tape armor layer, and a wear-resistant sheath layer.
[0007] Furthermore, the cable conductor is composed of five strands of copper wire twisted together.
[0008] Furthermore, the copper wire is T2 copper wire, 2-10mm, provided by Shanghai Xingnuo Industrial Co., Ltd.
[0009] Furthermore, the inner semiconductor shielding layer is conductive carbon black.
[0010] Furthermore, the conductive carbon black is Cabot BP2000 with a particle size of 15-30 nm, provided by Shanghai Jingyan Chemical Co., Ltd.
[0011] Furthermore, the insulating layer is made of polyvinyl chloride.
[0012] Furthermore, the polyvinyl chloride is P440, provided by Jinan Runyu Chemical Co., Ltd.
[0013] Furthermore, the outer semiconductor shielding layer is cross-linked polyethylene.
[0014] Furthermore, the cross-linked polyethylene is HDPE Dushanzi Petrochemical 8008H, provided by Shanghai Bangtao International Trade Co., Ltd.
[0015] Furthermore, the flame-retardant layer is a composite material of a flame retardant and an ethylene-vinyl acetate copolymer, and its preparation process is as follows: The flame retardant and ethylene-vinyl acetate copolymer were vacuum dried for 12-24 hours, mixed evenly, and then paraffin wax and silica powder were added. The mixture was then kneaded at 90-100℃ for 10-20 minutes to obtain a compound. The compound was then hot-pressed at 170-180℃ for 20-30 minutes at a pressure of 10-20 MPa to obtain a composite material of the flame retardant and ethylene-vinyl acetate copolymer.
[0016] Furthermore, the flame retardant is a mixture of zinc borate and ammonium polyphosphate.
[0017] Furthermore, the zinc borate is ZB-2235 with a particle size of 3-5 μm, and is provided by Shandong Chengshun Chemical Technology Co., Ltd.
[0018] Furthermore, the ammonium polyphosphate has a particle size of 200 mesh and a P2O5 content of ≥60%, and is provided by Shandong Chengshun Chemical Technology Co., Ltd.
[0019] Furthermore, the paraffin wax is a crystalline wax, provided by Wuxi Meiside Chemical Products Co., Ltd.
[0020] Furthermore, the silica powder has a particle size of 400-3000 mesh and is provided by Changxing Innovation Ultrafine Powder Co., Ltd.
[0021] Furthermore, the ethylene-vinyl acetate copolymer is LG EA19400 from South Korea, with a vinyl acetate content of 5-20%, and is provided by Shanghai Suwanye Plastics Co., Ltd.
[0022] Furthermore, the composite material of the flame retardant and the ethylene-vinyl acetate copolymer comprises the following components by weight: 100-110 parts of ethylene-vinyl acetate copolymer, 10-15 parts of zinc borate, 20-30 parts of ammonium polyphosphate, 4-6 parts of paraffin wax, and 3-5 parts of silica powder.
[0023] Furthermore, the inner lining is made of polyvinyl chloride.
[0024] Furthermore, the polyvinyl chloride is GM-RT-(50-120A), provided by Guangdong Guangsu Technology Co., Ltd.
[0025] Furthermore, the wear-resistant sheath layer is a polyurethane cable sheath material, and its preparation process is as follows: (1) Mix thermoplastic polyurethane with wear-resistant agent, castor oil, molybdenum disulfide and antioxidant, knead at 80-90℃ for 10-20 min, then add fumed silica, carbon fiber, vinyltriethoxysilane and flame retardant, knead at 90-100℃ for 1-2 h to obtain a mixture; (2) The mixture is extruded and granulated to obtain polyurethane cable sheath material.
[0026] Furthermore, the thermoplastic polyurethane used in step (1) is Covestro 192X from Germany, provided by Shanghai Jichengyuan Engineering Plastics Co., Ltd.
[0027] Furthermore, the wear-resistant agent in step (1) is CP-990, which is provided by Shanghai Zirun Chemical Additives Co., Ltd.
[0028] Furthermore, the castor oil in step (1) is refined grade 1 castor oil from India, provided by Guangdong Zhongrun Chemical Co., Ltd.
[0029] Furthermore, in step (1), the molybdenum disulfide is ZR053 with a particle size of 2000 mesh, provided by Henan Zhuorong Chemical Co., Ltd.
[0030] Furthermore, the antioxidant in step (1) is RIANOX 1010, provided by Tianjin Lianlong New Materials Co., Ltd.
[0031] Furthermore, the silica in step (1) has a particle size of 100-2000 mesh and is provided by Hebei Kexu Building Materials Co., Ltd.
[0032] Furthermore, in step (1), the carbon fiber is 9mm short-cut carbon fiber, provided by Polycarbonate (Guangdong) Co., Ltd.
[0033] Furthermore, in step (2), the extrusion granulation temperature is 150-180℃ and the rotation speed is 180-200r / min.
[0034] Furthermore, the polyurethane cable sheath material comprises the following weight components: 50-60 parts thermoplastic polyurethane, 10-15 parts fumed silica, 15-25 parts flame retardant, 3-5 parts abrasion resistant agent, 6-9 parts carbon fiber, 0.5-1.2 parts vinyltriethoxysilane, 1-3 parts castor oil, 1-2 parts molybdenum disulfide, and 0.2-2 parts antioxidant.
[0035] Furthermore, the preparation method of the flame retardant is as follows: Step A: Under nitrogen protection, dimethyl phosphite and dimethylvinylchlorosilane are mixed, chloroform solvent is added, and the mixture is stirred evenly. Then aluminum trichloride is added, and the mixture is heated to 50-60℃ and reacted for 10-14 hours. After the solvent is removed by evaporation, the mixture is hydrolyzed in distilled water for 30-60 minutes to obtain phosphorus-containing polysiloxane. Step B: Mix phosphorus-containing polysiloxane and 2-methyl-1,3-propanediol evenly, add triethylamine under nitrogen protection, heat to 70-85℃, react for 10-12 hours, cool to room temperature, filter, wash several times, and vacuum dry at 75-85℃ for 12-24 hours to obtain the flame retardant.
[0036] In the above technical solution, the PH bond in the phosphite undergoes an addition reaction with the C=C double bond in dimethylvinylchlorosilane to form a phosphorus-containing polysiloxane; the phosphorus-oxygen bond in the phosphorus-containing polysiloxane reacts with the hydroxyl functional group in 2-methyl-1,3-propanediol to generate a flame retardant containing phosphate ester groups. This flame retardant can effectively reduce the combustion performance of the polymer and improve its flame retardant effect.
[0037] Furthermore, in step A, the mass ratio of dimethyl phosphite to dimethyl vinylchlorosilane is 1:(1.3-1.6).
[0038] Furthermore, in step A, the mass of the chloroform solvent is 2-3 times the total mass of dimethyl phosphite and dimethylvinylchlorosilane.
[0039] Furthermore, in step A, the mass of aluminum trichloride is 0.5-1.0% of the total mass of dimethyl phosphite and dimethylvinylchlorosilane.
[0040] Furthermore, in step B, the mass ratio of phosphorus-containing polysiloxane and 2-methyl-1,3-propanediol is 1:(1.2-1.5).
[0041] Furthermore, in step B, the mass of triethylamine is 0.6-1.0% of the total mass of the phosphorus-containing polysiloxane and 2-methyl-1,3-propanediol.
[0042] A method for preparing a wear-resistant copper core cable includes the following steps: S1: Ethylene-vinyl acetate copolymer is extruded onto the cable conductor through a coating machine to form an inner semiconductor shielding layer. After cooling, chlorosulfonated polyethylene is extruded onto the surface of the inner semiconductor shielding layer to form an insulation layer. After cooling, cross-linked polyethylene is extruded onto the surface of the insulation layer to form an outer semiconductor shielding layer. Then, copper tape is wrapped around the outer semiconductor shielding layer to form a copper tape wrapped shielding layer. S2: A flame-retardant composite material and ethylene-vinyl acetate copolymer are extruded onto the surface of a copper tape wrapping shield to form a flame-retardant layer. After cooling, polyvinyl chloride is extruded onto its surface to form an inner liner. A layer of galvanized steel tape is wrapped around the inner liner to form a galvanized steel tape armor layer. Polyurethane cable sheath material is extruded onto the outside of the galvanized steel tape armor layer to form a wear-resistant sheath layer. After cooling, a wear-resistant copper core cable is obtained.
[0043] Furthermore, the extrusion process is as follows: extrusion speed: 5-10 m / min, extrusion temperature: between 150-250℃, and extrusion pressure: 10-20 MPa.
[0044] Furthermore, the thickness of the inner semiconductor shielding layer is 0.5-1.5 mm.
[0045] Furthermore, the thickness of the insulating layer is 3-5 mm.
[0046] Furthermore, the outer semiconductor shielding layer is 0.5-1.5 mm thick.
[0047] Furthermore, the copper strip wraps around the shielding layer for 0.8-1.5mm.
[0048] Furthermore, the copper strip is T2 purple ketone strip, provided by Shanghai Gengtuo Metal Products Co., Ltd.
[0049] Furthermore, the flame-retardant layer is 0.5-2.5mm thick.
[0050] Furthermore, the inner lining layer is 0.5-1.5mm thick. Furthermore, the galvanized steel strip armor layer is 0.3-2.0 mm thick.
[0051] Furthermore, the galvanized steel strip is St05Z and is provided by Shanghai Chiqi Industrial Co., Ltd.
[0052] Furthermore, the wear-resistant sheath layer has a thickness of 1.0-2.0 mm.
[0053] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. The wear-resistant copper core cable and its preparation method of the present invention, with the cable conductor as the center, are sequentially covered from the inside out with an inner semiconductor shielding layer, an insulation layer, an outer semiconductor shielding layer, a copper tape wrapped shielding layer, a flame-retardant layer, an inner lining layer, a galvanized steel tape armor layer, and a wear-resistant sheath layer; wherein the inner and outer semiconductor shielding layers can effectively prevent the electric and magnetic fields in the cable from interfering with surrounding equipment and circuits, improving the cable's anti-interference performance and signal transmission quality; the insulation layer is made of polyvinyl chloride, which has good insulation performance and voltage resistance, ensuring the safe and reliable operation of the cable; the copper tape wrapped shielding layer can further improve the cable's shielding performance and reduce electromagnetic interference from the outside of the cable; the flame-retardant layer can effectively prevent the cable from burning and spreading in a fire, improving the cable's safety performance; the inner lining layer and the wear-resistant sheath layer can protect the internal structure and external surface of the cable, improving the cable's wear resistance and service life.
[0054] 2. The wear-resistant copper core cable and its preparation method of the present invention involve an addition reaction between the PH bond in the phosphite and the C=C double bond in dimethylvinylchlorosilane to form a phosphorus-containing polysiloxane; the phosphorus-oxygen bond in the phosphorus-containing polysiloxane reacts with the hydroxyl functional group in 2-methyl-1,3-propanediol to generate a flame retardant containing phosphate ester groups. This flame retardant can effectively reduce the combustion performance of the polymer and improve its flame retardant effect. Using the flame retardant in the manufacture of polyurethane cable sheath materials imparts excellent flame retardant properties to them. Detailed Implementation
[0055] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0056] In this embodiment, the copper wire is T2 purple copper wire, 2mm-10mm, provided by Shanghai Xingnuo Industrial Co., Ltd.; the conductive carbon black is Cabot BP2000, with a particle size of 15-30nm, provided by Shanghai Jingyan Chemical Co., Ltd.; the polyvinyl chloride is P440, provided by Jinan Runyu Chemical Co., Ltd.; the cross-linked polyethylene is HDPE Dushanzi Petrochemical 8008H, provided by Shanghai Bangtao International Trade Co., Ltd.; the zinc borate is ZB-2235, with a particle size of 3-5μm, provided by Shandong Chengshun Chemical Technology Co., Ltd.; the ammonium polyphosphate has a particle size of 200 mesh and P2O5≥60%, provided by Shandong Chengshun Chemical Technology Co., Ltd.; the paraffin wax is crystalline wax, provided by Wuxi Meiside Chemical Products Co., Ltd.; the silica powder has a particle size of 400-3000 mesh, provided by Changxing Innovation Ultrafine Powder Co., Ltd.; and the ethylene-vinyl acetate copolymer is from LG Korea. EA19400 vinyl acetate content is 5-20%, supplied by Shanghai Suwanye Plastics Co., Ltd.; polyvinyl chloride is GM-RT-(50-120A), supplied by Guangdong Guangsu Technology Co., Ltd.; thermoplastic polyurethane is Covestro 192X from Germany, supplied by Shanghai Jichengyuan Engineering Plastics Co., Ltd.; wear-resistant agent is CP-990, supplied by Shanghai Zirun Chemical Additives Co., Ltd.; castor oil is refined grade 1 castor oil from India, supplied by Guangdong Zhongrun Chemical Co., Ltd.; molybdenum disulfide is ZR053, particle size 2000 mesh, supplied by Henan Zhuorong Chemical Co., Ltd.; antioxidant is RIANOX. 1010 is provided by Tianjin Lianlong New Material Co., Ltd.; the precipitated silica has a particle size of 100-2000 mesh and is provided by Hebei Kexu Building Materials Co., Ltd.; the carbon fiber is 9mm short-cut carbon fiber and is provided by Jusheng Carbon Fiber (Guangdong) Co., Ltd.; the copper strip is T2 purple ketone strip and is provided by Shanghai Gengtuo Metal Products Co., Ltd.; the galvanized steel strip is St05Z and is provided by Shanghai Chiqi Industrial Co., Ltd.
[0057] In the following examples and comparative examples, 1 part equals 10g.
[0058] Example 1: A method for preparing a wear-resistant copper core cable, comprising the following processes: S1: Ethylene-vinyl acetate copolymer is extruded onto the cable conductor through a coating machine to form an inner semiconductor shielding layer. After cooling, chlorosulfonated polyethylene is extruded onto the surface of the inner semiconductor shielding layer to form an insulation layer. After cooling, cross-linked polyethylene is extruded onto the surface of the insulation layer to form an outer semiconductor shielding layer. Then, copper tape is wrapped around the outer semiconductor shielding layer to form a copper tape wrapped shielding layer. S2: A flame-retardant composite material and ethylene-vinyl acetate copolymer are extruded onto the surface of a copper tape wrapping shield to form a flame-retardant layer. After cooling, polyvinyl chloride is extruded onto its surface to form an inner liner. A layer of galvanized steel tape is wrapped around the inner liner to form a galvanized steel tape armor layer. Polyurethane cable sheath material is extruded onto the outside of the galvanized steel tape armor layer to form a wear-resistant sheath layer. After cooling, a wear-resistant copper core cable is obtained.
[0059] The preparation process of the composite material of flame retardant and ethylene-vinyl acetate copolymer in S2 is as follows: Ten parts of zinc borate, 20 parts of ammonium polyphosphate, and 100 parts of ethylene-vinyl acetate copolymer were vacuum dried for 12 hours, mixed evenly, and then four parts of paraffin wax and three parts of silica powder were added. The mixture was then kneaded at 90°C for 10 minutes to obtain a compound. The compound was then hot-pressed at 170°C for 20 minutes at a pressure of 10 MPa to obtain a composite material of flame retardant and ethylene-vinyl acetate copolymer.
[0060] The preparation process of the polyurethane cable sheath material in S2 is as follows: (1) Under nitrogen protection, 5 parts of dimethyl phosphite and 6.5 parts of dimethyl vinyl chloride silane were mixed, 23 parts of chloroform solvent were added, and the mixture was mixed evenly. Then 0.06 parts of aluminum trichloride were added, heated to 50°C, and reacted for 10 h. After the solvent was removed by evaporation, the mixture was hydrolyzed in distilled water for 30 min to obtain phosphorus-containing polysiloxane. 10 parts of phosphorus-containing polysiloxane and 12 parts of 2-methyl-1,3-propanediol were mixed evenly. Under nitrogen protection, 0.13 parts of triethylamine were added, the temperature was raised to 70°C, and the reaction was carried out for 10 hours. After cooling to room temperature, the mixture was filtered, washed several times, and dried under vacuum at 75°C for 12 hours to obtain the flame retardant. (2) Mix 50 parts of thermoplastic polyurethane, 3 parts of wear-resistant agent, 1 part of castor oil, 1 part of molybdenum disulfide, and 0.2 parts of antioxidant, knead at 80°C for 10 min, then add 10 parts of silica, 6 parts of carbon fiber, 0.5 parts of vinyltriethoxysilane, and 15 parts of flame retardant, and knead at 90°C for 1 h to obtain a mixture; (3) The mixture is extruded and granulated to obtain polyurethane cable sheath material.
[0061] Example 2: A method for preparing a wear-resistant copper core cable, comprising the following processes: S1: Ethylene-vinyl acetate copolymer is extruded onto the cable conductor through a coating machine to form an inner semiconductor shielding layer. After cooling, chlorosulfonated polyethylene is extruded onto the surface of the inner semiconductor shielding layer to form an insulation layer. After cooling, cross-linked polyethylene is extruded onto the surface of the insulation layer to form an outer semiconductor shielding layer. Then, copper tape is wrapped around the outer semiconductor shielding layer to form a copper tape wrapped shielding layer. S2: A flame-retardant composite material and ethylene-vinyl acetate copolymer are extruded onto the surface of a copper tape wrapping shield to form a flame-retardant layer. After cooling, polyvinyl chloride is extruded onto its surface to form an inner liner. A layer of galvanized steel tape is wrapped around the inner liner to form a galvanized steel tape armor layer. Polyurethane cable sheath material is extruded onto the outside of the galvanized steel tape armor layer to form a wear-resistant sheath layer. After cooling, a wear-resistant copper core cable is obtained.
[0062] The preparation process of the composite material of flame retardant and ethylene-vinyl acetate copolymer in S2 is as follows: 12 parts of zinc borate, 25 parts of ammonium polyphosphate and 105 parts of ethylene-vinyl acetate copolymer were vacuum dried for 12 hours, mixed evenly, and then 5 parts of paraffin wax and 4 parts of silica powder were added. The mixture was then kneaded at 95°C for 15 minutes to obtain a compound. The compound was then hot-pressed at 175°C for 25 minutes at a pressure of 15 MPa to obtain a composite material of flame retardant and ethylene-vinyl acetate copolymer.
[0063] The preparation process of the polyurethane cable sheath material in S2 is as follows: (1) Under nitrogen protection, 10 parts of dimethyl phosphite and 14 parts of dimethyl vinyl chlorosilane were mixed, 36 parts of chloroform solvent were added, the mixture was mixed evenly, and then 0.19 parts of aluminum trichloride were added. The mixture was heated to 55°C and reacted for 12 hours. After the solvent was removed by evaporation, the mixture was hydrolyzed in distilled water for 45 minutes to obtain phosphorus-containing polysiloxane. 20 parts of phosphorus-containing polysiloxane and 28 parts of 2-methyl-1,3-propanediol were mixed evenly. Under nitrogen protection, 0.38 parts of triethylamine were added, the temperature was raised to 80°C, and the reaction was carried out for 11 hours. After cooling to room temperature, the mixture was filtered, washed several times, and dried under vacuum at 80°C for 18 hours to obtain the flame retardant. (2) Mix 55 parts of thermoplastic polyurethane, 4 parts of abrasion resistant agent, 2 parts of castor oil, 1.5 parts of molybdenum disulfide, and 1 part of antioxidant, knead at 85°C for 15 minutes, and then add 12 parts of silica, 7 parts of carbon fiber, and 0.9 parts of vinyl triethylene glycol. A mixture was prepared by kneading oxysilane and 20 parts of flame retardant at 95°C for 1.5 hours. (3) The mixture is extruded and granulated to obtain polyurethane cable sheath material.
[0064] Example 3: A method for preparing a wear-resistant copper core cable, comprising the following processes: S1: Ethylene-vinyl acetate copolymer is extruded onto the cable conductor through a coating machine to form an inner semiconductor shielding layer. After cooling, chlorosulfonated polyethylene is extruded onto the surface of the inner semiconductor shielding layer to form an insulation layer. After cooling, cross-linked polyethylene is extruded onto the surface of the insulation layer to form an outer semiconductor shielding layer. Then, copper tape is wrapped around the outer semiconductor shielding layer to form a copper tape wrapped shielding layer. S2: A flame-retardant composite material and ethylene-vinyl acetate copolymer are extruded onto the surface of a copper tape wrapping shield to form a flame-retardant layer. After cooling, polyvinyl chloride is extruded onto its surface to form an inner liner. A layer of galvanized steel tape is wrapped around the inner liner to form a galvanized steel tape armor layer. Polyurethane cable sheath material is extruded onto the outside of the galvanized steel tape armor layer to form a wear-resistant sheath layer. After cooling, a wear-resistant copper core cable is obtained.
[0065] The preparation process of the composite material of flame retardant and ethylene-vinyl acetate copolymer in S2 is as follows: 15 parts zinc borate, 30 parts ammonium polyphosphate and 110 parts ethylene-vinyl acetate copolymer were vacuum dried for 24 hours, mixed evenly, and then 6 parts paraffin wax and 5 parts silica powder were added. The mixture was then kneaded at 100°C for 20 minutes to obtain a compound. The compound was then hot-pressed at 180°C for 30 minutes at a pressure of 20 MPa to obtain a composite material of flame retardant and ethylene-vinyl acetate copolymer.
[0066] The preparation process of the polyurethane cable sheath material in S2 is as follows: (1) Under nitrogen protection, 10 parts of dimethyl phosphite and 16 parts of dimethyl vinyl chlorosilane were mixed, 78 parts of chloroform solvent were added, the mixture was mixed evenly, and then 0.26 parts of aluminum trichloride were added. The mixture was heated to 60°C and reacted for 14 hours. After the solvent was removed by evaporation, the mixture was hydrolyzed in distilled water for 60 minutes to obtain phosphorus-containing polysiloxane. 20 parts of phosphorus-containing polysiloxane and 30 parts of 2-methyl-1,3-propanediol were mixed evenly. Under nitrogen protection, 0.5 parts of triethylamine were added, the temperature was raised to 85°C, and the reaction was carried out for 12 hours. After cooling to room temperature, the mixture was filtered, washed several times, and dried under vacuum at 85°C for 24 hours to obtain the flame retardant. (2) Mix 60 parts of thermoplastic polyurethane, 5 parts of wear-resistant agent, 3 parts of castor oil, 2 parts of molybdenum disulfide, and 2 parts of antioxidant, knead at 90°C for 20 min, then add 15 parts of silica, 9 parts of carbon fiber, 1.2 parts of vinyltriethoxysilane, and 25 parts of flame retardant, and knead at 100°C for 2 h to obtain a mixture; (3) The mixture is extruded and granulated to obtain polyurethane cable sheath material.
[0067] Comparative Example 1: The polyurethane cable sheath material comprises the following components by weight: 50 parts thermoplastic polyurethane, 10 parts fumed silica, 15 parts flame retardant, 6 parts carbon fiber, 0.5 parts vinyltriethoxysilane, 1 part castor oil, 1 part molybdenum disulfide, and 0.2 parts antioxidant. No abrasion resistant agent is added to Comparative Example 1. Other steps and processes are the same as in Example 1.
[0068] Comparative Example 2: The polyurethane cable sheath material comprises the following weight components: 50 parts thermoplastic polyurethane, 15 parts flame retardant, 6 parts carbon fiber, 0.5 parts vinyltriethoxysilane, 1 part castor oil, 1 part molybdenum disulfide, and 0.2 parts antioxidant. Comparative Example 2 does not contain abrasion resistant agent or silica. Other steps and processes are the same as in Example 1.
[0069] Comparative Example 3: Compared with Example 2, Comparative Example 3 replaced the flame retardant in step (1) with magnesium hydroxide of the same specification, while the other steps and processes were the same as in Example 2.
[0070] Comparative Example 4: A method for preparing a wear-resistant copper core cable, comprising the following processes: Compared with Example 2, the preparation process of the polyurethane cable sheath material in S2 of Comparative Example 4 is as follows: (1) Under nitrogen protection, 28 parts of dimethyl phosphite and 7 parts of dimethyl vinyl chloride silane were mixed, 36 parts of chloroform solvent were added, and the mixture was mixed evenly. Then 0.19 parts of aluminum trichloride were added, heated to 55°C, and reacted for 12 hours. After the solvent was removed by evaporation, the mixture was hydrolyzed in distilled water for 45 minutes to obtain phosphorus-containing polysiloxane. 20 parts of phosphorus-containing polysiloxane and 28 parts of 2-methyl-1,3-propanediol were mixed evenly. Under nitrogen protection, 0.38 parts of triethylamine were added, the temperature was raised to 80°C, and the reaction was carried out for 11 hours. After cooling to room temperature, the mixture was filtered, washed several times, and dried under vacuum at 80°C for 18 hours to obtain the flame retardant. (2) Mix 55 parts of thermoplastic polyurethane, 4 parts of abrasion resistant agent, 2 parts of castor oil, 1.5 parts of molybdenum disulfide, and 1 part of antioxidant, knead at 85°C for 15 minutes, and then add 12 parts of silica, 7 parts of carbon fiber, and 0.9 parts of vinyl triethylene glycol. A mixture was prepared by kneading oxysilane and 20 parts of flame retardant at 95°C for 1.5 hours. (3) The mixture is extruded and granulated to obtain polyurethane cable sheath material.
[0071] Compared with Example 2, in Comparative Example 4, the mass ratio of dimethyl phosphite to dimethylvinylchlorosilane was 1:4, and the remaining steps were the same as in Example 2.
[0072] Comparative Example 5: A method for preparing a wear-resistant copper core cable, comprising the following processes: S1: Ethylene-vinyl acetate copolymer is extruded onto the cable conductor through a coating machine to form an inner semiconductor shielding layer. After cooling, chlorosulfonated polyethylene is extruded onto the surface of the inner semiconductor shielding layer to form an insulation layer. After cooling, cross-linked polyethylene is extruded onto the surface of the insulation layer to form an outer semiconductor shielding layer. Then, copper tape is wrapped around the outer semiconductor shielding layer to form a copper tape wrapped shielding layer. S2: A flame-retardant composite material and ethylene-vinyl acetate copolymer are extruded onto the surface of a copper tape wrapping shield to form a flame-retardant layer. After cooling, polyvinyl chloride is extruded onto its surface to form an inner liner. A layer of galvanized steel tape is wrapped around the inner liner to form a galvanized steel tape armor layer. Polyethylene cable sheath material is extruded onto the outside of the galvanized steel tape armor layer to form a wear-resistant sheath layer. After cooling, a wear-resistant copper core cable is obtained.
[0073] Compared with Example 2, Comparative Example 5 replaced the polyurethane cable sheath material with polyethylene cable sheath material of the same specification, deleted the preparation process of the polyurethane cable sheath material, and kept other processes and steps unchanged.
[0074] experiment
[0075] The wear-resistant copper core cables obtained in Examples 1-3 and Comparative Examples 1-5 were used to prepare samples, and their performance was tested and the test results were recorded. According to GB / T 18380.11-2022 "Cables and Optical Cables - Combustion Tests under Flame Conditions - Part 11: Test Apparatus for Vertical Flame Spread Test of Single Insulated Wires and Cables", the flame retardant performance was determined. The experimental procedure was as follows: the sample length was 600mm, the width was 50mm, and the thickness was ≥1.5mm. The sample was fixed on the testing device, and its position and height were adjusted to meet the standard requirements. The sample was ignited, and the start time of combustion and various parameters during the combustion process were recorded. Class A combustion performance indicates a non-combustible material; such components do not ignite, smolder, or char when exposed to open flame or high temperature in air. Class B1 combustion performance indicates a flame-retardant material; it is difficult to ignite, smolder, or char when exposed to open flame or high temperature in air, and combustion or smoldering immediately ceases after the flame source is removed. Class B2 combustion performance indicates a combustible material; it ignites immediately or smolders when exposed to open flame or high temperature in air, and continues to burn or smolder after the flame source is removed.
[0076] According to GB / T 2951.21 "General Test Methods for Insulation and Sheath Materials of Cables and Optical Fibers", the abrasion resistance was determined. The experimental procedure was as follows: A sheath specimen with a length of 200 mm, a width of 20 mm, and a thickness of 3 mm was prepared. The test was conducted using a grinding wheel abrasion tester with a diameter of 150 mm, a width of 25 mm, and a hardness of H18-20. The grinding wheel load was 2.5 N, the specimen load was 2 N, and the abrasion head rotation speed could be selected from 60-100 rpm. Data such as the mass loss and wear depth of the specimen were recorded.
[0077] The tensile strength was determined according to GB / T 2951.1 "General Test Methods for Insulation and Sheath Materials of Cables and Optical Fibers". The test procedure was as follows: the specimen length was 100 mm, the clamp moving speed was (250±50) mm / min, the test was started, and the maximum tensile force was measured and recorded during the test.
[0078]
[0079] Based on the data in the table above, the following conclusions can be clearly drawn: 1. Compared with Comparative Examples 1 and 2, the wear amount and tensile strength of the samples in Examples 1-3 were reduced, indicating that the addition of wear-resistant agents and silica can significantly improve the wear resistance of polyurethane cable sheath materials, thereby improving the wear resistance and service life of the cable.
[0080] 2. Compared with Examples 1-3, the flame retardant properties of Comparative Examples 3 and 4 are significantly reduced. It can be seen that the flame retardant properties of the polyurethane cable sheath material prepared by the present invention are affected by the ratio of dimethyl phosphite to dimethyl vinylchlorosilane. By selecting the raw material ratio within the range described above, the prepared cable has excellent flame retardant properties.
[0081] 3. Compared with Examples 1-3, the flame retardant properties, tensile strength, and abrasion resistance of the product obtained in Comparative Example 5 all decreased, indicating that polyurethane cable sheath material has better performance than polyethylene cable sheath material.
[0082] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process method article or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process method article or apparatus.
[0083] Finally, it should be noted that the above descriptions are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A wear-resistant copper core cable, characterized in that: The cable is centered on the cable conductor and is covered from the inside out with an inner semiconductor shielding layer, an insulation layer, an outer semiconductor shielding layer, a copper tape wrapping shielding layer, a flame retardant layer, an inner lining layer, a galvanized steel tape armor layer, and a wear-resistant sheath layer. The wear-resistant sheath layer is a polyurethane cable sheath material, and its preparation method is as follows: (1) Mix thermoplastic polyurethane with wear-resistant agent, castor oil, molybdenum disulfide and antioxidant, knead at 80-90℃ for 10-20 min, then add fumed silica, carbon fiber, vinyltriethoxysilane and flame retardant, knead at 90-100℃ for 1-2 h to obtain a mixture. (2) The mixture is extruded and granulated to obtain polyurethane cable sheath material; The flame retardant is prepared as follows: Step A: Under nitrogen protection, dimethyl phosphite and dimethylvinylchlorosilane are mixed, chloroform solvent is added, and the mixture is stirred evenly. Then aluminum trichloride is added, and the mixture is heated to 50-60℃ and reacted for 10-14 hours. After the solvent is removed by evaporation, the mixture is hydrolyzed in distilled water for 30-60 minutes to obtain phosphorus-containing polysiloxane. Step B: Mix phosphorus-containing polysiloxane and 2-methyl-1,3-propanediol evenly, add triethylamine under nitrogen protection, heat to 70-85℃, react for 10-12 hours, cool to room temperature, filter, wash several times, and vacuum dry at 75-85℃ for 12-24 hours to obtain the flame retardant.
2. The wear-resistant copper core cable according to claim 1, characterized in that: The cable conductor is made of five strands of copper wire twisted together.
3. The wear-resistant copper core cable according to claim 1, characterized in that: The inner semiconductor shielding layer is conductive carbon black.
4. The wear-resistant copper core cable according to claim 1, characterized in that: The insulating layer is made of polyvinyl chloride.
5. The wear-resistant copper core cable according to claim 1, characterized in that: The flame-retardant layer is a composite material of a flame retardant and an ethylene-vinyl acetate copolymer, and its preparation process is as follows: The flame retardant and ethylene-vinyl acetate copolymer were vacuum dried for 12-24 hours, mixed evenly, and then paraffin wax and silica powder were added. The mixture was then kneaded at 90-100℃ for 10-20 minutes to obtain a compound. The compound was then hot-pressed at 170-180℃ for 20-30 minutes at a pressure of 10-20 MPa to obtain a composite material of the flame retardant and ethylene-vinyl acetate copolymer.
6. The wear-resistant copper core cable according to claim 1, characterized in that: The inner lining is made of polyvinyl chloride.
7. A method for preparing a wear-resistant copper core cable according to any one of claims 1-6, characterized in that: Includes the following steps: S1: Extruding conductive carbon black onto the cable conductor forms an inner semiconductor shielding layer. After cooling, extruding polyvinyl chloride onto the surface of the inner semiconductor shielding layer forms an insulation layer. After cooling, extruding cross-linked polyethylene onto the surface of the insulation layer forms an outer semiconductor shielding layer. Then, wrapping copper tape around the outer semiconductor shielding layer forms a copper tape wrapped shielding layer. S2: A flame-retardant composite material and ethylene-vinyl acetate copolymer are extruded onto the surface of a copper tape wrapping shield to form a flame-retardant layer. After cooling, polyvinyl chloride is extruded onto its surface to form an inner liner. A layer of galvanized steel tape is wrapped around the inner liner to form a galvanized steel tape armor layer. Polyurethane cable sheath material is extruded onto the outside of the galvanized steel tape armor layer to form a wear-resistant sheath layer. After cooling, a wear-resistant copper core cable is obtained.
Citation Information
Patent Citations
Halogen-free flame-retardant cable sheath material
CN103849062A
Anti-aging and anti-twisting wind power cable
CN105778469A
Fire -retardant fire -resistant high temperature resistant electrified for track traffic midium voltage cable of fire control
CN204884649U